2011
DOI: 10.1002/stco.201110013
|View full text |Cite
|
Sign up to set email alerts
|

Toughness requirements for plastic design with structural steel

Abstract: This report deals with the results of an international research project ”Plastotough”, the aim of which is to discover the toughness requirements for structural steel to make it suitable for plastic design for ”static loads” and for loads that vary over time, as from seismic events. These toughness requirements should be specified as the Charpy energy value KVUS in the upper shelf domain of the toughness‐temperature diagram and as the extension of KVUS to the minimum temperature TUS for which it is still valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Considering the maximum effective number of cycles, it is obvious that the effects of the cycles produced by seismic excitation belong to the lower limit of the ultra-low-cycle fatigue (Kanvinde and Deierlein 2004). As a consequence, the damage curves for earthquake effects are similar with the one of monotonic loads (Feldman et al 2011). The low cycle fatigue is characterized by a slope, corresponding to the reducing effects of the cyclic loading.…”
Section: Ultra Low Cycle Fatigue and Monotonic Loadsmentioning
confidence: 63%
See 2 more Smart Citations
“…Considering the maximum effective number of cycles, it is obvious that the effects of the cycles produced by seismic excitation belong to the lower limit of the ultra-low-cycle fatigue (Kanvinde and Deierlein 2004). As a consequence, the damage curves for earthquake effects are similar with the one of monotonic loads (Feldman et al 2011). The low cycle fatigue is characterized by a slope, corresponding to the reducing effects of the cyclic loading.…”
Section: Ultra Low Cycle Fatigue and Monotonic Loadsmentioning
confidence: 63%
“…The fracture of the buckled flanges of the wide flange steel sections under a cycle loading has been studied by Yamada et al (1988); Kanvinde and Deierlein (2004); Feldman et al (2011). The fracture strains decrease when the number of cycles increases due the low cycle fatigue.…”
Section: Typology Of Cyclic Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be shown that the cracking associ ated with ultra-low-cycle fatigue is not relevant for buildings, as long as the behavior is determined using reasonable limits for inter-story drift. For seismic issues these material performance investigations demonstrate that an elevated level of toughness is an appropriate solution (Feldmann et al, 2011a). Bridges with integral abutments are characterized by two unique features.…”
Section: Toughness Requirements Formentioning
confidence: 99%